Identification of Successful Delivery Factors for Stakeholder Management in Public-Private Partnerships Projects in Malaysia - Kaharuddin, Sakinah Khalidah; Adnan, Hamimah; Baharuddin, Har Einur Azrin (International Journal of Sustainable Construction Engineering and Technology, 2021)
Public-Private Partnerships (PPP) have been common in civil engineering works involving public and private sectors. PPP manages complex projects and involves multiple stakeholders. Stakeholders in the PPP project need to be properly managed to achieve project goals, minimise risk, and accommodate stakeholders' interest. Poor management of stakeholder could lead to project failure. Hence, this paper aims to identify stakeholder management's success factors towards successfully delivering PPP infrastructure projects in Malaysia. A quantitative approach via questionnaires survey was conducted on 70 respondents from multiple stakeholders' backgrounds, namely public authority, consultants, contractors, and financiers involved in PPP infrastructure projects in Malaysia. The survey was provided to the respondents with a list of the success factors. The responders were asked to rate the success factors contributing to successful delivery factors for stakeholder management based on the scale provided. The result concluded from four (4) stages of stakeholder engagement: stakeholder analysis, stakeholder engagement, stakeholder management action plan, and monitoring. A list of success factors for successful stakeholder management was developed by showing the relationship between stakeholder management and success factors. This component encapsulated the success factors perceived as the success factors contributing to the successful delivery of stakeholder management in Malaysia. The finding highlights on four (4) stakeholder management issues that need to be focused in PPP infrastructure projects. These include the need for a good stakeholder management process, the strategy to engage the stakeholders through clear and honest communication, a proper project communication plan to oversee overlapping in the process, and to monitor relationships of stakeholders during operations.